2015
DOI: 10.1039/c4dt02624a
|View full text |Cite
|
Sign up to set email alerts
|

Process for the synthesis of symmetric and unsymmetric oxygen bridged dimers of boron subphthalocyanines (μ-oxo-(BsubPc)2s)

Abstract: A process for the gram scale synthesis of the oxygen bridged dimer of boron subphthalocyanine, μ-oxo-(BsubPc)2, has been developed. During the development it was found that a wide range of reaction pathways under diverse conditions lead to μ-oxo-(BsubPc)2 formation. However, obtaining μ-oxo-(BsubPc)2 as the main reaction product in appreciable yields and its subsequent isolation were extremely challenging. The best balance of purity, yield and conversion was achieved with a time controlled reaction of an equim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…A more time-efficient synthetic procedure for the BsubPc acceptor used in this study (PhO-Cl 6 BsubPc) was adapted from Ebenhoch et al, based on our synthetic methodology. ,, Rather than refluxing phenol with Cl–Cl 6 BsubPc in toluene for 7 days, we have previously found that bromine in the axial position of BsubPc is more labile than chlorine and, thus, undergoes a faster reaction . Therefore, bromo-hexachloro-boron-subphthalocyanine (Br-Cl 6 BsubPc) was first synthesized.…”
Section: Methodsmentioning
confidence: 99%
“…A more time-efficient synthetic procedure for the BsubPc acceptor used in this study (PhO-Cl 6 BsubPc) was adapted from Ebenhoch et al, based on our synthetic methodology. ,, Rather than refluxing phenol with Cl–Cl 6 BsubPc in toluene for 7 days, we have previously found that bromine in the axial position of BsubPc is more labile than chlorine and, thus, undergoes a faster reaction . Therefore, bromo-hexachloro-boron-subphthalocyanine (Br-Cl 6 BsubPc) was first synthesized.…”
Section: Methodsmentioning
confidence: 99%
“…BsubPcs contain a boron center surrounded by three nitrogen-linked isoindoline groups, which form a unique bowl shape. We have proven experimentally that the physical properties of BsubPcs, such as maximum absorption wavelength, sublimation temperature, solubility, , melting point, crystal structure, extinction coefficient, and electronic characteristics, can be altered through the functionalization of the axial position or substitution of the hydrogens in the periphery. This array of modifications is highly desirable compared with the inability to alter the electronic and optical properties of typical fullerene electron acceptors, which are limited to an open-circuit voltage ( V OC ) of <1 V in OPVs …”
Section: Introductionmentioning
confidence: 99%
“…We have now decided to systematically investigate the detailed electrochemical properties of Cl-F 6 BsubPc, Cl-F 12 BsubPc, F-F 12 BsubPc, and F-F 6 BsubPc, together with the established Cl-BsubPc, F-BsubPc, Cl-Cl 6 BsubPc, and Cl-Cl 12 BsubPc as additional points of comparison. This became feasible after having described the improved synthesis of F-F 12 BsubPc and F-F 6 BsubPc and how to obtain all herein-studied compounds in high analytical purity .…”
mentioning
confidence: 99%